Citrus pulp and enzyme complex for growing and finishing pigs - Amorim, Alessandro Borges; Thomaz, Maria Cristina [UNESP]; Ruiz, Urbano Do Santos [UNESP]; Martinez, Juliana Freitas [UNESP]; Pascoal, Leonardo Augusto Fonseca; Daniel, Everton [UNESP]; Watanabe, Pedro Henrique; Rosalen, David Luciano [UNESP] (UFBA - Universidade Federal da Bahia, 2014)
The purpose is to evaluate the effects of levels of citrus pulp (CP), over the aperformance and the carcass characteristics, with or without the addition of an enzyme complex in the feed. Seventy-two pigs were used, at 25.71 ± 7.51kg initial body weight (BW) and 98.81 ± 10.64kg final BW. The diets were formulated for the stages: 1 - 70 to 101; 2 - 102 to 130; 3 - 131 to 143 days of age. Because there was no redistribution of the animals in blocks at the beginning of stages 2 and 3, the data were evaluated at the periods: 1 - 70 to 101; 2 - 70 to 130; and 3 - 70 to 143 days of age. The inclusion of up to 15% of CP, with or without the addition of an enzyme complex in the diets, decreased the daily feed intake in Periods 1 and 2, and improved feed:gain in Period 2; however, the animals showed adaptive responses in Period 3. In the absence of the enzyme complex, the carcass yield and the fat/meat ratio decreased linearly as the levels of CP increased. In the presence of the enzyme complex, the fat/meat ratio had a quadratic behavior, and the level of 7.78% of CP determined the lowest ratio. The inclusion of up to 15% of CP with or without the addition of the enzyme complex in diets no differences in performance; therewith, it can be a feed alternative, without effect on the carcass characteristics.

Objetivou-se avaliar os efeitos de níveis de polpa cítrica (PC), com ou sem adição de um complexo enzimático nas rações, sobre o desempenho dos suínos e as características de carcaça. Utilizou-se 72 suínos, com 25,71 ± 7,51 e 98,81 ± 10,64kg de pesos inicial e final, respectivamente. As dietas foram formuladas para as fases: 1 - 70 aos 101; 2 - 102 aos 130; 3 - 131 aos 143 dias de idade. Como não houve redistribuição dos animais nos blocos no início das fases 2 e 3, os dados foram avaliados nos períodos: 1 - 70 aos 101; 2 - 70 aos 130 e 3 - 70 aos 143 dias de idade. A inclusão de até 15% de PC, com ou sem a adição do complexo enzimático nas dietas, diminuiu o consumo diário de ração nos Períodos 1 e 2, e melhorou a conversão alimentar no Período 2, porém, os animais apresentaram respostas adaptativas no Período 3. O rendimento de carcaça e a relação gordura/carne diminuíram linearmente, na medida em que aumentaram os níveis de PC, na ausência do complexo enzimático. Na presença do produto, a relação gordura/carne apresentou comportamento quadrático, e o nível de 7,78% de PC determinou a menor relação. A inclusão de até 15% de PC com ou sem a adição do complexo enzimático nas dietas para suínos, não proporciona diferenças no desempenho e pode ser uma alternativa alimentar, sem afetar as características de carcaça.
Polpa cítrica e complexo enzimático para suínos na fase de crescimento e terminação
Keywords: desempenho; enzimas exógenas; ingrediente alternativo; tipificação de carcaça; alternative ingredient; carcass classification; exogenous enzymes; performance